1998
DOI: 10.1021/ic980342u
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of a Stable trans-Dioxo Tungsten(IV) Complex and Series of Mono-Oxo Molybdenum(IV) and Tungsten(IV) Complexes. Structural and Electronic Effects of π-Bonding in trans-[M(O)(X)(dppe)2]+/0 Systems

Abstract: trans-[W(O)(F)(dppe)(2)](BF(4)) (dppe = Ph(2)PCH(2)CH(2)PPh(2), 1,2-bis(diphenylphosphino)ethane) (10) has been synthesized. From this, the neutral trans-[W(O)(2)(dppe)(2)].2CH(3)OH (11) was prepared by a hydrolysis and deprotonation reaction with Et(4)NOH in methanol/water. Together with the analogous molybdenum compound (2) this compound afforded by substitution under acid conditions salts of trans-[M(O)(X)(dppe)(2)](+) ions (M = Mo, W; X = OH, OCH(3), Cl, Br, I, NCS) and trans-[Mo(O)(N(3))(dppe)(2)](CF(3)SO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 59 publications
2
19
0
Order By: Relevance
“…of 1-fluoro-2,4,6-trimethylpyridinium tetrafluoroborate, a reagent acting as net source of “F + ”, to a solution of [Mo(PNP Me -Ph)(CO) 3 ] in CH 2 Cl 2 yielded the analogous fluorine complex [Mo(PNP Me -Ph)(CO) 2 F 2 ] ( 3d ) in 93% isolated yield (Scheme 3). The long reaction time required (3 days) and the high yield of this reaction clearly suggest that the BF 4 − counterion acts as an additional fluoride source which has indeed precedence in molybdenum and tungsten chemistry [11].…”
Section: Resultsmentioning
confidence: 89%
“…of 1-fluoro-2,4,6-trimethylpyridinium tetrafluoroborate, a reagent acting as net source of “F + ”, to a solution of [Mo(PNP Me -Ph)(CO) 3 ] in CH 2 Cl 2 yielded the analogous fluorine complex [Mo(PNP Me -Ph)(CO) 2 F 2 ] ( 3d ) in 93% isolated yield (Scheme 3). The long reaction time required (3 days) and the high yield of this reaction clearly suggest that the BF 4 − counterion acts as an additional fluoride source which has indeed precedence in molybdenum and tungsten chemistry [11].…”
Section: Resultsmentioning
confidence: 89%
“…These observations are not surprising, because the (W=O) 4+ core is not easily converted into the ( cis ‐WO 2 ) 2+ core, typical for dioxo–metal cores of d 0 transition metals 22. Similar to the formation of organic coordination complexes of WO 4+ and WO 2 2+ , commonly synthesized by ligand exchange starting from WOCl 4 and WO 2 Cl 2 , respectively,23,25 the conversion between the two P 2 W 20 families requires the initial degradation of the original crystal into PW 9 and W units followed by the in situ formation of the alternative core and consequent precipitation of the other family. This procedure was demonstrated by Contant,20 who showed that both K 10 [P 2 W 20 O 70 (OH 2 ) 2 ] and K 13 [KP 2 W 20 O 72 ] can be converted into K 6 [P 2 W 21 O 71 (OH 2 ) 3 ] by boiling a solution of these salts in 1 M HCl.…”
Section: Introductionmentioning
confidence: 98%
“…1 The molecular structure of 1S 2 . 33 In this study, the two W(IV) complexes structures have axially compressed octahedral structures with four long bonds in xy-planes (S1, S2, N8, N11 in 1dt and S1, S2, N8, N22 in 4dt) and two shorter ones (O1, O2) along z axes. Thermal ellipsoids are presented at the 30% probability level (applies to all presented X-ray structures).…”
Section: Synthesismentioning
confidence: 82%
“…For strongly tetragonally compressed octahedral d 2 complexes the orbital splitting is known to result the singlet ground state system with both electrons on the d xy orbital. 33 In this study, the two W(IV) complexes structures have axially compressed octahedral structures with four long bonds in xy-planes (S1, S2, N8, N11 in 1dt and S1, S2, N8, N22 in 4dt) and two shorter ones (O1, O2) along z axes. This leads to a diamagnetic, singlet ground state with two electrons on d xy orbital.…”
Section: Synthesismentioning
confidence: 82%